Assessing asthma symptoms in children: qualitative research supporting the development of the Pediatric Asthma Diary-Child (PAD-C) and Pediatric Asthma Diary-Observer (PAD-O) - Helena Bradley; Claire Trennery; Amy M. Jones; Aoife Lydon; Frances White; Rebecca Williams-Hall; Rob Arbuckle; Erin Tomaszewski; Vivian H. Shih; John Haughney; Amanda Eisen; Tonya Winders; et al. (SpringerOpen, 2023)
Abstract Background Pediatric asthma has been identified by regulators, clinicians, clinical trial sponsors, and caregivers as an area in need of novel fit-for-purpose clinical outcome assessments (COAs) developed in accordance with the U.S. Food and Drug Administration's (FDA's) regulatory guidance for evaluating clinical benefit in treatment trials. To address this gap, the Patient-Reported Outcome (PRO) Consortium's Pediatric Asthma Working Group has continued development of 2 COAs to assess asthma signs and symptoms in pediatric asthma clinical trials to support efficacy endpoints: a PRO measure, the Pediatric Asthma Diary-Child (PAD-C) for children 8-11 years old (y.o.) and an observer-reported outcome measure, the Pediatric Asthma Diary-Observer (PAD-O) for caregivers of children 4-11 y.o. This qualitative research aimed to generate evidence regarding the content validity of the PAD-C and PAD-O. Methods Semi-structured combined concept elicitation and cognitive interviews were conducted with a diverse sample of U.S. participants (15 children 8-11 y.o. and 30 caregivers of children 4-11 y.o.). All children had clinician-diagnosed mild to severe asthma. Interviews explored the experience of pediatric asthma and assessed the understanding and relevance of both measures. Interviews were conducted across 3 iterative rounds to allow for modifications. Results Concept elicitation findings demonstrated that the core sign/symptom and impact concepts assessed in the PAD-C (cough, hard to breathe, out of breath, wheezing, chest tightness, and nighttime awakenings/symptoms) and PAD-O (cough, difficulty breathing, short of breath, wheezing, and nighttime awakenings/signs) correspond to those most frequently reported by participants; concept saturation was achieved. All PAD-C and PAD-O instructions and core items were well understood and considered relevant by most participants. Feedback from participants, the Pediatric Asthma Working Group, advisory panel, and FDA supported modifications to the measures, including addition of 1 new item to both measures and removal of 1 caregiver item. Conclusions Findings provide strong support for the content validity of both measures. The cross-sectional measurement properties of both measures and their user experience and feasibility in electronic format will be assessed in a future quantitative pilot study with qualitative exit interviews, intended to support the reliability, construct validity, final content, and, ultimately, FDA qualification of the measures.